2009
DOI: 10.1007/s10535-009-0003-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abscisic acid on photosynthetic parameters during ex vitro transfer of micropropagated tobacco plantlets

Abstract: The aim of this research was to determine whether exogenous abscisic acid (ABA) applied immediately after ex vitro transfer of in vitro grown plants can improve their acclimatization. Tobacco (Nicotiana tabacum L.) plantlets were transferred into pots with Perlite initially moistened either by water or 50 μM ABA solution and they were grown under low (LI) or high (HI) irradiance of 150 and 700 μmol m -2 s -1 , respectively. Endogenous content of ABA in tobacco leaves increased considerably after ABA applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
34
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 59 publications
9
34
0
Order By: Relevance
“…Each parameters were measured before ex vitro transfer and after ex vitro transfer. Means ± SE, n = 20 propagated tobacco plantlets (Pospisilova et al 2009a). Higher chlorophyll a+b content was also observed when ABA was applied immediately after ex vitro transfer (Pospisilova et al 2009a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each parameters were measured before ex vitro transfer and after ex vitro transfer. Means ± SE, n = 20 propagated tobacco plantlets (Pospisilova et al 2009a). Higher chlorophyll a+b content was also observed when ABA was applied immediately after ex vitro transfer (Pospisilova et al 2009a).…”
Section: Resultsmentioning
confidence: 99%
“…Means ± SE, n = 20 propagated tobacco plantlets (Pospisilova et al 2009a). Higher chlorophyll a+b content was also observed when ABA was applied immediately after ex vitro transfer (Pospisilova et al 2009a). Chlorophyll a+b content in ABA-treated plants increased not only in persistent leaves but also new leaves developed at 2 weeks after ex vitro transfer (Pospisilova et al 1998).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been found to be a main physiological signal in inducing drought and high salinity responses (Farooq et al 2009 ;Lata and Prasad 2011 ). The role of ABA is not only in the regulation of developmental pathways but also for controlling many stress adaptation responses like activating genes responsible for osmotic adjustment, ion compartmentalization, root hydraulic conductivity, regulation of shoot and root growth, limiting transpiration rate and wilting, and ultimately reducing water loss in the plants (Verslues and Zhu 2005 ;Pospíšilová et al 2009 ). It is also involved in modifi cation of gene expression and upregulation of various stress-responsive genes during osmotic imbalance (Ingram and Bartels 1996 ).…”
Section: Role Of Aba and Transcription Factors In Osmotic Stress Signmentioning
confidence: 99%
“…In previous experiments ABA was applied immediately after ex vitro transfer of in vitro grown tobacco plantlets, and it was found that chlorophyll (a+b) and β-carotene contents were higher in ABA-treated plants, but the content of xanthophyll cycle pigments was not increased. However, the degree of xanthophyll cycle pigments deepoxidation was decreased what also suggested less stress in ABA-treated plants (Pospíšilová et al 2009). A combined application of ABA and osmoticum is a routine method for stimulating somatic embryo maturation.…”
Section: Introductionmentioning
confidence: 99%
“…The relative water loss from detached leaves of in vitro grown Aronia arbutifolia, Tagetes erecta or tobacco plantlets was reduced by addition of ABA into culture medium (Colón-Guasp et al 1996, Pospíšilová 1996, Aguilar et al 2000. Addition of ABA to the substrate immediately after transplantation of in vitro grown tobacco plants also alleviated their wilting (Pospíšilová et al 1998(Pospíšilová et al , 2000(Pospíšilová et al , 2009.…”
Section: Introductionmentioning
confidence: 99%